Pembuatan Sensor Suhu Berbahan Kawat Kumparan dengan Indikator Intensitas Cahaya - Moh. Toifur Toifur; Zulfana Dina; Okimustava (Universitas Nurul Huda, 2022)
This study aims to make a temperature sensor using coil wire with an indicator in the form of light intensity and to test the sensitivity of iron, copper, and nichrome wires in responding to changes in temperature. The temperature sensor unit consists of a coil of 250 turns, connected in series with a 3V/32W DC lamp and a 3 volt constant voltage source. As a medium, a room illuminated by a 100 watt lamp was used, where the lamp voltage is adjusted from 50 V to 150 V via slide regulator to produce a medium temperature from 30°C to 100°C, while for the indicator lamps, the light intensity of the lamp is measured with a luxmeter UT383. The results showed that there was a significant relationship between changes in medium temperature to light intensity for copper and iron coils while the nichrome coil is not. From the linear regression on temperature and light intensity data, the sensor sensitivity of copper and iron wire coils is (1.34 ±0.06) lux/°C and (7.33 ± 0.43) lux/°C, respectively. From these values can be known that the temperature sensor of the iron coil is more sensitive than copper, but the copper coil is more precise in indicating temperature than the iron coil. From this research, a temperature sensor unit made of copper and iron coils has been successfully made to measure the temperature of the medium from 30°C to 100°C using a light intensity indicator.